Artificial Placenta - Lung Assist Devices for Term and Preterm Newborns with Respiratory Failure. Issue 6 (June 2013) - Rochow, Niels; Chan, Emily C.; Wu, Wen-I; Selvaganapathy, Ponnambalam R.; Fusch, Gerhard; Berry, Leslie; Brash, John; Chan, Anthony K.; Fusch, Christoph
Respiratory insufficiency is a major cause of neonatal mortality and long-term morbidity, especially in very low birth weight infants. Today, non-invasive and mechanical ventilation are commonly accepted procedures to provide respiratory support to newborns, but they can reach their limit of efficacy. To overcome this technological plateau and further reduce mortality rates, the technology of an "artificial placenta", which is a pumpless lung assist device connected to the umbilical vessels, would serve to expand the therapeutic spectrum when mechanical ventilation becomes inadequate to treat neonates with severe respiratory insufficiency. The first attempts to create such an artificial placenta took place more than 60 years ago. However, there has been a recent renaissance of this concept, including developments of its major components like the oxygenator, vascular access via umbilical vessels, flow control, as well as methods to achieve hemocompatibility in extracorporeal circuits. This paper gives a review of past and current development, animal experiments and human case studies of artificial placenta technology.